Analysis Of Sustainable Tourism Policies In Pandeglang Regency - Sjaiful Akbar; Nugroho, Arif; Satrio Anggoro, Riyan; Meirani, Riska; Dwi Amaliah, Kholydiah; Dhelaylah, Dhelaylah (Jurnal Scientia, 2024)
The tourism potential in Pandeglang Regency is very high. Based on this potential, the local government is working to develop tourist villages in the regency through Regional Regulation No. 12 of 2021. The management of tourist villages is aimed at improving the local economic conditions and fostering sustainable tourism. This analysis is conducted to understand the implementation of these regulations in Pandeglang Regency. The method used for this analysis is descriptive qualitative, which involves explaining the collected information into an analysis. The data used comprises both primary and secondary data obtained from literature reviews and online media. Based on the analysis, the sustainable tourism policy in Pandeglang Regency has not been effectively implemented, though the policy has triggered improvements in the economic conditions of the related villages. The conclusion of this study is that the tourist villages in Pandeglang Regency have strengths in their diverse natural wealth. However, weaknesses exist in the human resources and infrastructure sectors, opportunities for becoming new tourist destinations, and threats to environmental and cultural sustainability.